L'expérience de la différence religieuse dans l'Europe moderne (XVIe - XVIIIe siè-cles) - Forclaz, Bertrand (Editions Alphil Presses universitaires suisses, 2013)
This collective work explores the themes of religious coexistence and the broaching of religious frontiers in Europe during the 16th, 17th and 18th Centuries. It intends to open new areas for discussion on a European level through the bias of a dia-logue between researchers subscribing to highly different national traditions (France, Netherlands, Switzerland, and Germany). It acts through the contributions gathered here to analyse the possibilities and different methods of interfaith con-tact by using as a departure point the experience of religious differences: The ex-perience garnered by diverse social actors - ecclesiastical, magisterial, academics and nobility.